Correlation analysis between Cortisol levels and Noise Pollution - Lily Montesinos-Valencia (2021)
To determine the Cortisol levels in patients with renal pathology in hospitalization and Emergency areas correlated to sound contamination.Material and Methods: A prospective and correlational study was performed, whereas Pearson correlation coefficient was used. In addition, noise was determined with the Casella sound level meter and cortisol concentration with the Immuno-Chemo-lumidity test. Cortisol concentration was 23.58 µg/dl in Emergency patients and 12.94 µg/dl in hospitalization patients. There as a significant difference (p<0.05). Emergency noise pollution was 61.94 dB (A) and 55.10 dB(A) in Hospitalization, establishing a significant difference (p<0.05). The relationship between Cortisol concentration and noise pollution in emergency and hospitalization patients as examined, and it was found that the higher the Cortisol concentration, the higher the noise level, with a significant difference (p<0.05). In sum, there is a significant correlation (r = 0.754) between Cortisol concentration and noise pollution in emergency patients, as well as there is a significant correlation ( r = 0.763) between Cortisol concentration and noise pollution in hospitalization patients